The Relations between Repetitive Behaviors and Family Accommodation among Children with Autism: A Mixed-Methods Study - Gal Shiloh; Eynat Gal; Ayelet David; Elkana Kohn; Ariela Hazan; Orit Stolar (MDPI AG, 2023)
Restricted and repetitive behaviors and interests (RRBI) are a significant component in diagnosing autism spectrum disorder (ASD). They often pose the main challenge in day-to-day functions for children with ASD and their families. Research addressing family accommodation behaviors (FAB) in the ASD population is scarce, and associations with the characteristics of the children's behaviors are unclear. This sequential mixed-methods study assessed the correlation between RRBI and FAB within the ASD group to deepen the understanding of parents' subjective experiences regarding their children's RRBI. It included a quantitative phase with a follow-up qualitative study. A total of 29 parents of children with autism (5-13 yr) completed the study questionnaires; a total of 15 also were interviewed regarding their children's RRBI and related FAB. We used the Repetitive Behavior Scale-Revised (RBS-R) to assess RRBI, and the Family Accommodation Scale (FAS-RRB) to assess FAS. In-depth interviews from phenomenological methodology were used in the qualitative phase. We found significant positive correlations between the RRBI and FAB overall and their subscores. Qualitative research supports these findings, adding descriptive examples of the accommodations families make to address the RRBI-related challenges. The results indicate relations between RRBI and FAB and the importance of practically addressing children with autism's RRBI and their parents' experiences. Both affect and are affected by the children's behaviors.